2017
DOI: 10.3168/jds.2016-12473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of denatured whey protein concentrate and its fractions on cheese composition and rheological properties

Abstract: The objectives of this study were (1) to assess the effect of a denatured whey protein concentrate (DWPC) and its fractions on cheese yield, composition, and rheological properties, and (2) to separate the direct effect of the DWPC or its fractions on cheese rheological properties from the effect of a concomitant increase in cheese moisture. Semihard cheeses were produced at a laboratory scale, and mechanical properties were characterized by dynamic rheometry. Centrifugation was used to induce a moisture gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…However, as the protein source is not casein-rich, no immediate conclusions on the effect of such increments on a possible improved cheese yield and dry matter content can be made, as it has been previously reported when either milk protein concentrates or isolates are used [33] , [34] . The inclusion of whey proteins in cheesemilk is a common practice in some industries, especially in denatured form [35] and as protein aggregates [21] .…”
Section: Resultsmentioning
confidence: 99%
“…However, as the protein source is not casein-rich, no immediate conclusions on the effect of such increments on a possible improved cheese yield and dry matter content can be made, as it has been previously reported when either milk protein concentrates or isolates are used [33] , [34] . The inclusion of whey proteins in cheesemilk is a common practice in some industries, especially in denatured form [35] and as protein aggregates [21] .…”
Section: Resultsmentioning
confidence: 99%
“…At the 60 th day of ripening the ratio Pdm/M of RF+CB showed values for similar to FF cheeses while in all other cases this ratio presented signi cantly higher values, which adversely affected texture. Perreault et al (2017) assessed the effect of denatured whey protein concentrate (DWPC) and its fractions on cheese yield, composition, and rheological properties of cheeses. For cheeses with the same moisture content, the use of DWPC had no direct effect on rheological parameters.…”
Section: Resultsmentioning
confidence: 99%
“…For cheeses with the same moisture content, the use of DWPC had no direct effect on rheological parameters. The protein aggregates were primarily responsible for the increase in cheese yield while moisture content explained, to a large extent, the variation in cheese rheological properties [35]. Other authors evaluated the fat mimicking mechanism of MWP in milk-based systems using rheological and tribological techniques, and reported that friction levels attained with MPW proteins and dairy fat at typical speeds involved in oral processing were comparable, demonstrating therefore the capability of MWP dispersions to imitate dairy fat in milk-based systems from a lubrication point of view [36].…”
Section: Milkmentioning
confidence: 99%